The relationship between lyrics and melody case study: My Heart Will Go On by James Horner and Will Jennings, and Because You Loved Me by Diane Warren / Alia Farahin Abd Wahab - Abd Wahab, Alia Farahin (2009)
Popular music is probably the most commonly well received genre of music today. In my opinion, this is most likely since popular music is easily accessible via radio, television, and the World Wide Web. Thus, popular music, especially songs; have coincidently become part of our daily lives; which brings me to my next point: research objectives .My main objective in conducting this research on the subject matter of the relationship between lyrics and melody; is to understand the concept of lyric writing more in depth. For instance, composers often overlook the lyric writing concept, and focus mainly towards the writing of melody instead. The fact of the matter is, a lot of popular songs are accepted and/or well received mostly because of excellent construction of memorable lyrics. In addition, I am especially interested in understanding the concept of a "winning".